CONTRIBUTO PARA O ESTUDO DA NEOLITIZAÇÃO NO ALENTEJO CENTRAL: O POVOAMENTO MAIS ANTIGO NA ÁREA DE MORA (PORTUGAL) - Rocha, Leonor (2017)
The archaeological sites of Barroca 1 and Chaminé 3, located near the river Raia, were identified in 2005 by Leonor Rocha and Manuel Calado, in the work done on the preparation of the Archaeological Sites of the municipality of Mora (Calado, Rock and Alvim, 2012). In 2006 and 2007, surveys carried out in two sites brought new data on the settlement and the relationship Mesolithic / Neolithic this region. Although it places very disturbed by successive episodes of affectations of agricultural / forest character, the stratigraphy observed and materials collected indicate un occupation that have started in the Mesolithic and finished somewhere in the middle Neolithic.